"HIDE AND SEEK" NEUROSENSORY RETINAL DETACHMENTS IN PERIPAPILLARY PACHYCHOROID SYNDROME ASSOCIATED WITH PULMONARY ARTERIAL HYPERTENSION. Issue Volume 16:Issues 1(2022) (21st November 2019) - Govetto, Andrea; Sarraf, David; Scialdone, Antonio
Abstract : In peripapillary pachychoroid syndrome associated with pulmonary arterial hypertension, a combination of hemodynamic choroidal alterations and increased central venous pressure may lead to the accumulation of peripapillary subretinal and intraretinal fluid. Central venous pressure variations with posturing may be responsible for the spontaneous resolution of these abnormalities. Abstract : Purpose: To report the case of a patient with peripapillary pachychoroid syndrome and recurrent and spontaneous resolving peripapillary neurosensory retinal detachments associated with pulmonary arterial hypertension. Methods: Case report imaged with spectral-domain optical coherence tomography, swept-source optical coherence tomography angiography, fundus autofluorescence, and fluorescein and indocyanine green angiography. Results: A 47-year-old woman presented with unilateral blurred vision and metamorphopsia in her left eye and was diagnosed with peripapillary serous retinal detachments associated with peripapillary pachychoroid syndrome. Cardiologic examination was remarkable for heart failure secondary to severe pulmonary arterial hypertension. Neurosensory detachments spontaneously resolved after 1 day but recurred again three days from baseline. Fluorescein and indocyanine green angiography illustrated choroidal hyperpermeability associated with pachyvessels, whereas optical coherence tomography angiography displayed numerous areas of choriocapillaris nonperfusion, more severe in the left eye of the patient. Conclusion: In pulmonary arterial hypertension, hemodynamic changes caused by increased central venous pressure and endothelin-1 may explain the development of exudative retinal detachment and choroidal ischemia. The pathophysiological mechanisms explaining the peripapilary location of the fluid and the thick choroid, as with the peripapillary pachychoroid syndrome, are explored and discussed.